021 Developing new performance indicators for ambulance service category B calls. Issue 3 (1st March 2011) - Turner, Janette; Bjarkoy, Mike
Abstract : Background: Historically ambulance service performance measurement has been based in time based standards. Whilst time is a significant issue related to clinical outcome for some life-threatening calls this makes up only a small proportion of ambulance service workload and there are many other calls where time has no impact on outcome. The development of alternative performance indicators that reflect the quality and appropriateness as well as the timeliness of pre-hospital care is one of the key recommendations of 'Taking Healthcare to the Patient'. Clinical performance indicators have been developed for category A calls. This project has been designed to extend this work to category B calls. Methods: The study is being conducted in several stages using a mixed methods approach. Quantitative analysis of routine category B call data to explore the characteristics of category B calls. Development of a framework to structure indicator development. A consensus workshop to generate ideas for potential performance indicators. A Delphi survey to identify an agreed set of indicators for further testing. Pilot studies to test the usefulness of new indicators and assess the practical implications of implementation. Results to date: The project is still in progress. To date the first 3 steps have been completed. Analysis of routine data has found that: 50% of category B call volume is within 5 of the 32 dispatch categories. 18/32 categories account for 96% of calls. Half of patients have some assessment and only about 10% some intervention. A framework for indicator development has been constructed for broad clusters of patients using a number of dimensions that reflect quality care, for example clinical assessment & management, dispatch, destination and patient reported outcomes. The consensus workshop has been conducted and the results are currently being analysed.